Identification and analysis of ship carbon emission hotspots based on data field theory: A case study in Wuhan Port. (15th March 2023) - Zhou, Chunhui; Huang, Hongxun; Liu, Zongyang; Ding, Yiran; Xiao, Jinli; Shu, Yaqing
Abstract: Carbon peaking and carbon neutrality in the shipping industry are hot topics but now facing serious challenges. One of them is the current lack of scientific guidance on ship carbon reduction. Precise identification of carbon emission hotspot areas and ship types in ports is the key to controlling carbon emissions from ships. In this paper, a method of identifying and extracting ship carbon emission hotspots based on data field theory is proposed. Based on the theory of field in physics, the spatiotemporal aggregation pattern of ship carbon emissions in the port region is analyzed with regard to the characteristics of ship emission trajectory data. Taking Wuhan Port as an example, we successfully extracted the ship's carbon emission hotspot area based on the proposed method and analyzed the spatial and temporal dynamics of the ship's carbon emission hotspot in the area from several perspectives. The method proposed in this paper can be further applied to coastal ports, which is conducive to exploring the distribution of carbon emission hotspots and the spatial and temporal variation patterns of ships in China's ports. It provides scientific guidance for relevant departments to formulate and implement policies to reduce carbon emissions from ports, and promotes the early realization of the dual carbon goal of China's shipping industry.